KEDUDUKAN MAJELIS KEHORMATAN DISIPLIN KEDOKTERAN INDONESIA (MKDKI) DAN KONSIL KEDOKTERAN INDONESIA (KKI) DALAM PENEGAKAN DISIPLIN KEDOKTERAN DI INDONESIA (Studi Putusan Mahkamah Agung RI Nomor: 298K/TUN/2012) - Andryawan . (Faculty of Law - Tarumanagara University, 2016)
Health is one of human rights and the constitutional rights of every citizen of Indonesia. Government as manager of the Republic of Indonesia, are obligated to protect and guarantee the right to health care for all citizens without exception. One of them through the provision of services of the ministry of health by doctors. As a key element in the administration of medical practice, so the importance of the role of doctors and often leads to the assumption that the doctor is a